Analysis of pantun writing skills of class v students of SDN Sirnagalih 2 - Yolanda Marsha Santoso (LADU: Journal of Languages and Education, 2022)
Background: Skills are the focus of experts, one of the skills that must be achieved is the skill of writing rhymes. Purpose: this study aims to determine the extent to which students are able to make poetry works that are carried out at SDN SIRNAGALIH 2, Bogor Regency. Design and methods: The type of research method used in this research is Descriptive Qualitative Method. Results: The results of the analysis of several rhymes written by class V students have fulfilled the theoretical rhyme requirements (Masruchin, 2017). However, a rhyme that rhymes a-a-a-a is found, but the results of this paper can still be said to be a rhyme because it is in accordance with the theory (Attas, 2022) and (Pasaribu, 2021). The students' rhymes written in one line have 6-14 syllables but are still said to be rhymes because they are in accordance with the theory (Riandi, 2020) and (Mutohharoh et al., 2018). It can be concluded that not all rhymes written by students of class V at SDN SIRNAGALIH 2 meet the theoretical rhyme requirements (Masruchin, 2017).